2017
DOI: 10.1007/s00280-017-3245-5
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1 study of anti-TGFβ receptor type-II monoclonal antibody LY3022859 in patients with advanced solid tumors

Abstract: Purpose LY3022859 is an anti-TGFβRII IgG1 monoclonal antibody that inhibits receptor-mediated signaling activation. The primary objective of this phase I study was to determine a phase II dose in patients with advanced solid tumors. Secondary objectives were to assess safety and pharmacokinetics (PK). Methods LY3022859 was infused intravenously (IV) at 1.25 mg/kg over 1 hour every 2 weeks (Q2W) (cohort 1A) and at flat doses of 12.5 mg (cohort 1B) and 25 mg (cohort 2) over 3 hours Q2W. Results Fourteen pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 17 publications
0
55
0
Order By: Relevance
“…Neutralization of TGF- with M7824 can potentially increase therapeutic efficacy and reduce the safety concerns associated with other therapies targeting the TGF- pathway, such as anti-TGF- antibodies, anti-TGF- receptor antibodies, and TGF-RI kinase inhibitors (80)(81)(82). In a phase 1 study of an anti-TGF-RII human IgG1 monoclonal antibody (LY3022859), dose escalation beyond 25 mg (flat dose) was considered unsafe because of uncontrolled cytokine release, despite prophylactic treatment (83). In addition, in a phase 1 study of the TGF- antibody fresolimumab (GC1008), treatmentemergent cutaneous lesions with characteristics of keratoacanthomas (KAs) were observed, as well as a single case of squamous cell carcinoma (84).…”
Section: Discussionmentioning
confidence: 99%
“…Neutralization of TGF- with M7824 can potentially increase therapeutic efficacy and reduce the safety concerns associated with other therapies targeting the TGF- pathway, such as anti-TGF- antibodies, anti-TGF- receptor antibodies, and TGF-RI kinase inhibitors (80)(81)(82). In a phase 1 study of an anti-TGF-RII human IgG1 monoclonal antibody (LY3022859), dose escalation beyond 25 mg (flat dose) was considered unsafe because of uncontrolled cytokine release, despite prophylactic treatment (83). In addition, in a phase 1 study of the TGF- antibody fresolimumab (GC1008), treatmentemergent cutaneous lesions with characteristics of keratoacanthomas (KAs) were observed, as well as a single case of squamous cell carcinoma (84).…”
Section: Discussionmentioning
confidence: 99%
“…Pirfenidone, another small molecule, is also discussed to be involved in inhibition of TGFBR2 [57]. LY3022859, an anti-TGFBR2 IgG1 monoclonal antibody was developed by Eli Lilly Company and was investigated in several Phase I trials but was not further propagated because of clinical immune side effects (uncontrolled cytokine release) [58]. To date it remains unclear whether these side effects were due to reaction to antibody-protein epitopes or due to a complete shut-down of TGFβ signaling.…”
Section: Discussionmentioning
confidence: 99%
“…153 TR1 or IMC-TR1 (LY3022859) is another fully human anti-TβRII monoclonal antibody developed by Eli-Lilly & Co, tested in clinical trials in patients with advanced solid tumors. 157 As regards liver tumors, Dituri et al reported a different response in an HCC preclinical model between IMC-TR1 and galunisertib (LY2157299, Eli-Lilly & Co), suggesting that receptor expression on tumor cells is only one aspect in the patients selection approach and microenvironment, and that immune cell expression for this receptor should be taken into consideration. 158…”
Section: Inhibiting the Tgf-β Signaling Pathwaymentioning
confidence: 99%